Preparation method and application of sugarcane bagasse lignin nanoparticles and carbon quantum dots

CN118620616BActive Publication Date: 2026-11-03JIANGSU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410654807.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2026-11-03
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

Existing technologies for the separation and high-value utilization of lignin resources suffer from environmental pollution and damage to the lignin structure. In particular, lignin is prone to condensation under acidic conditions, which affects its preparation and application in nanoparticles and carbon quantum dots.

Method used

Sugarcane bagasse was treated with a diol eutectic solvent. By mixing choline chloride, oxalic acid dihydrate and diols with different carbon chain lengths, sugarcane bagasse lignin nanoparticles and carbon quantum dots were prepared. This avoided the addition of exogenous nitrogen sources, simplified the production process and improved performance.

Benefits of technology

It effectively inhibits lignin condensation, maintains structural integrity, improves the accessibility and utilization of lignin, broadens its application potential in nanotechnology and heavy metal detection, and realizes the diversified and high-value utilization of lignin resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118620616B_ABST
    Figure CN118620616B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of sugarcane bagasse lignin nanoparticles and carbon quantum dots, and belongs to the technical field of efficient utilization of biomass resources, and comprises the following steps: firstly, preparing a binary alcohol-based deep eutectic solvent; then, pretreating the sugarcane bagasse by using the deep eutectic solvent to separate lignin; and then, preparing the lignin nanoparticles and the carbon quantum dots through specific steps. The application is environment-friendly and low in cost, and the prepared lignin nanoparticles and carbon quantum dots have wide application prospects in multiple fields, including heavy metal safety detection and biomedical imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of efficient utilization technology of biomass resources, specifically relating to a method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots and their applications. Background Technology

[0002] Lignin, the second largest organic polymer in nature, is a three-dimensional amorphous polymer composed of phenylpropane structural units linked by ether and carbon-carbon bonds. Due to its abundant carbonyl, phenolic hydroxyl, and alcoholic hydroxyl groups, this polymer has shown great potential in various fields such as construction, food, packaging, and printing. However, traditional biomass processing technologies often require harsh conditions, such as the use of strong acids or high temperatures. This not only pollutes the environment but may also destroy the natural structure of lignin molecules, forming condensed lignin, thus hindering its value-added utilization in downstream applications.

[0003] Eutectic solvents (DES), as an emerging class of green solvents, are typically eutectic mixtures formed by hydrogen bond acceptors (HBAs) and hydrogen bond donors (HBDs) through hydrogen bonding. Common HBAs include quaternary ammonium salts such as choline chloride (ChCl), while HBDs may be organic acids (such as lactic acid, oxalic acid, and malic acid) or alcohols (such as ethylene glycol and glycerol). Due to their good biocompatibility, DES can stabilize sugars and furan derivatives through hydrogen bonding interactions and exhibits good biocompatibility with enzymes, making them a potential alternative to traditional solvents. HBDs in eutectic solvents can form hydrogen bonds with the three major components of biomass, weakening the hydrogen bonding interactions between these components, selectively dissolving hemicellulose and lignin, while essentially not dissolving cellulose, thus achieving effective separation of biomass components. Therefore, many researchers use DES to treat biomass resources and effectively separate lignin. For example, Hou et al. found the effects of HBDs with different numbers of hydroxyl groups, such as xylitol, ethylene glycol, and glycerol, on rice straw pretreatment. HBDs with more hydroxyl groups, such as glycerol, increased the system viscosity and reduced the solubility of lignin (DOI: 10.1016 / j.biortech.2017.10.019). Compared with neutral alcohol-based DES, acidic DES performed better in separating lignin. However, when using acidic DES to separate lignin, studies have found that under acidic high-temperature conditions, lignin side chains easily generate a large number of free radicals. These free radicals can form stable carbon-carbon bonds with themselves or adjacent lignin structures, initiating lignin condensation, which reduces the activity of the condensed lignin and makes it difficult to dissolve.

[0004] Related studies have found that adding ethylene glycol as an HBD to acidic DES systems can effectively inhibit lignin condensation. Yu et al., when treating poplar flour with a eutectic solvent of choline chloride, oxalic acid, and ethylene glycol, not only increased cellulose yield but also improved enzymatic hydrolysis efficiency. During this process, ethylene glycol modified the separated lignin side chains, reducing the occurrence of condensation reactions. The addition of ethylene glycol reduced the acidity and viscosity of the system, while simultaneously reducing cellulose degradation and lignin condensation (DOI: 10.1039 / D2GC00264G). Nevertheless, the effects of diols with different carbon chain lengths on the structure and properties of lignin have not been fully studied. This invention designs a series of diol DES with different carbon chain lengths for the separation and extraction of lignin from bagasse, filling this research gap.

[0005] Lignin nanoparticles (LNPs) and carbon quantum dots (CQDs) are two important nanoscale materials based on lignin. LNPs, with their unique physicochemical properties such as biodegradability, antioxidant properties, and UV shielding, have attracted significant attention in environmental protection, medicine, and chemical industries. Compared with other methods, the direct solvent nanoprecipitation method can rapidly produce LNPs in large quantities, showing significant advantages. CQDs, as carbon nanomaterials with dimensions smaller than 10 nm, have broad application prospects in many high-tech fields due to their wide availability of raw materials, low cost, and excellent performance. However, although existing patents (such as CN 115232176 A, CN 116716751 A) describe methods for extracting lignin from biomass resources, and techniques for preparing carbon quantum dots and micro / nanospheres using lignin derivatives (such as CA 117024784 A, CN 115678551 A), comprehensive research on the entire process from biomass component separation to nanomaterial preparation is still lacking. This invention aims to extract lignin from sugarcane bagasse using diol eutectic solvents and explore its applications in the preparation of nanoparticles and carbon quantum dots, particularly its potential in heavy metal detection. This invention not only demonstrates the environmental friendliness and significant advantages of diol eutectic solvents in lignin extraction and conversion but also showcases the enormous potential of CQDs in developing novel fluorescent probes. Furthermore, this invention provides a new perspective and strategy for the efficient utilization of lignin resources and their application in sustainable environmental governance, broadening the application scope of lignin in nanotechnology and heavy metal safety detection. It has significant scientific value and practical implications for promoting the high-value utilization of biomass resources. Summary of the Invention

[0006] The purpose of this invention is to address the problem of efficient separation and high-value utilization of existing lignin resources by disclosing a method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, which is carried out according to the following steps:

[0007] (1) Preparation of diol eutectic solvent: Choline chloride, oxalic acid dihydrate and diol are mixed in a certain proportion and stirred under heating conditions until all components are completely dissolved and uniformly mixed, thereby obtaining diol eutectic solvent.

[0008] (2) Sugarcane bagasse pretreatment: Sugarcane bagasse is mixed with a diol eutectic solvent for lignin separation. After the pretreatment is completed, an aqueous ethanol solution is added to the system and stirred. Then, the ethanol in the filtrate is removed by filtration and rotary evaporation to obtain a lignin-eutectic solvent mixture.

[0009] (3) Separation of lignin: Add deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir. After settling, filter again and wash the solid to obtain sugarcane bagasse lignin and eutectic solvent aqueous solution.

[0010] (4) Preparation of lignin nanoparticles: Dissolve the sugarcane bagasse lignin prepared in step (3) in anhydrous ethanol, remove insoluble matter by filtration, and then add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to obtain lignin nanoparticles (LNPs).

[0011] (5) Preparation of carbon quantum dots: The eutectic solvent aqueous solution obtained in step (3) is subjected to rotary evaporation to remove excess water, and then transferred to a hydrothermal reactor for hydrothermal reaction. After dialysis and filtration, carbon quantum dot solution (CQDs) is obtained.

[0012] In step (1), the molar ratio of choline chloride, oxalate dihydrate and diol is 1:1-2:0.2-1; the water bath heating temperature is 80-100℃, and the stirring time is 1-3h; the diol is one of ethylene glycol, 1-3 propylene glycol, 1-4 butanediol and 1-5 pentanediol.

[0013] In step (2), the pretreatment process is as follows: sugarcane bagasse and diol-based eutectic solvent are added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20, heated at 80-120℃ for 4-6 hours, and after the reaction is completed, the treatment liquid is transferred to a beaker with 100mL of 70wt% ethanol solution, stirred at room temperature for 2 hours, and then vacuum filtered; the rotary evaporation conditions are: 40℃, 90mbar.

[0014] In step (3), the volume of deionized water added is 10 times the volume of lignin-eutectic solvent, and the mixture is stirred for 0.5-2 hours and allowed to settle for 8-12 hours.

[0015] In step (4), the sugarcane bagasse lignin ethanol solution has a concentration of 1 mg / mL and is filtered through a 0.45 μm PTFE filter. After adding deionized water, the ethanol concentration in the sugarcane bagasse lignin ethanol solution is 50%.

[0016] In step (5), the rotary evaporation conditions are 40℃ and 90 mbar; the hydrothermal reaction temperature is 180-220℃ and the time is 6-10 h; after the reaction, centrifugation is performed, and the supernatant is filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate is transferred to a dialysis bag with a molecular weight cutoff of 500-3000 Da, and deionized water is used as the dialysis solution, with a dialysis time of 48-72 h.

[0017] This invention also claims protection for the sugarcane bagasse lignin nanoparticles and carbon quantum dots prepared by the above method in the heavy metal Fe 3+ Applications in safety detection. The application method is as follows: based on the fluorescence intensity of the CQDs solution with respect to Fe... 3+ The concentration of Fe decreases with increasing concentration and shows a linear correlation, thus obtaining the Fe concentration in the system. 3+ concentration.

[0018] Compared with the prior art, the beneficial effects of the present invention are:

[0019] (1) The present invention uses a diol eutectic solvent to extract lignin from sugarcane bagasse. Compared with common binary or ternary eutectic solvents, the addition of diols more effectively inhibits the condensation reaction of lignin. This characteristic not only maintains the structural integrity of lignin, but also improves the applicability of lignin in the subsequent preparation of nanoparticles and carbon quantum dots.

[0020] (2) Investigate the effects of a series of diol eutectic solvent pretreatments with different carbon chain lengths (C2-C5) on the structure and properties of sugarcane bagasse lignin.

[0021] (2) In the preparation process of CQDs, the present invention uses choline chloride in the eutectic solvent as a nitrogen source to successfully prepare nitrogen-doped lignin carbon quantum dots, avoiding the addition of exogenous nitrogen sources, simplifying the production process, reducing the preparation cost, realizing the secondary utilization of the eutectic solvent, and improving the performance of carbon quantum dots.

[0022] (3) This invention not only improves the accessibility and utilization of lignin extracted from biomass, but also successfully develops multifunctional LNPs and CQDs, which have broad application potential in multiple fields, realizing the diversified and high-value utilization of lignin resources. Attached Figure Description

[0023] Figure 1 This is a flowchart of the preparation process of the present invention;

[0024] Figure 2 This is a transmission electron microscope (TEM) image of the lignin nanoparticles 4C-LNPs prepared in Example 1;

[0025] Figure 3 This is a TEM image of the carbon quantum dots 4C-CQDs prepared in Example 1.

[0026] In the figure, a - TEM image and size distribution histogram; b - high-resolution TEM image;

[0027] Figure 4 These are photographs of the carbon quantum dot 4C-CQDs solution prepared in Example 1 under different illuminations and fluorescence spectra at different excitation wavelengths.

[0028] Figure labels: a - photographs under sunlight and ultraviolet light, b - fluorescence spectra at different excitation wavelengths (250-390 nm), c - fluorescence spectra of carbon quantum dots in Examples 1-4 and comparative examples at an excitation wavelength of 316 nm;

[0029] Figure 5 This is the X-ray electron spectrum (XPS) of the carbon quantum dots 4C-CQDs prepared in Example 1;

[0030] Figure 6 The carbon quantum dots 4C-CQDs prepared in Example 1 are subjected to different concentrations of Fe. 3+ Fluorescence spectrum and linear relationship graph,

[0031] The figure shows the fluorescence intensity of the α-carbon quantum dot solution as a function of Fe. 3+ Concentration changes (0-1000 μmol / L), b-fluorescence intensity changes and Fe 3+ Linear relationship curve of concentration. Detailed Implementation

[0032] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings, but the embodiments and protection scope of the present invention are not limited thereto.

[0033] Example 1:

[0034] A method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, specifically including the following steps:

[0035] (1) Mix choline chloride, oxalate dihydrate and 1,4-butanediol in a molar ratio of 1:1:0.2 and stir in an 80°C water bath for 1 hour until all components are completely dissolved and uniformly mixed. Name it 4C-DES.

[0036] (2) Sugarcane bagasse and 4C-DES were added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20. The mixture was heated at 80°C for 4 hours. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70 wt% ethanol solution. The mixture was stirred at room temperature for 2 hours and then vacuum filtered. The filtrate was evaporated by rotary evaporation at 40°C and 90 mbar to obtain a lignin-eutectic solvent mixture.

[0037] (3) Add 10 times the volume of deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir for 0.5 h. After standing and settling for 8 h, filter again and wash the obtained solid to obtain sugarcane bagasse lignin (4C-L) and eutectic solvent aqueous solution.

[0038] (4) Dissolve 4C-L in anhydrous ethanol to prepare a concentration of 1 mg / mL. Filter through a 0.45 μm PTFE filter to remove insoluble matter. Then, add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to make the ethanol concentration 50% to obtain lignin nanoparticles, named 4C-LNPs.

[0039] (5) The eutectic solvent aqueous solution obtained in step (3) was rotary evaporated at 40°C and 90 mbar to remove excess water. Then, it was transferred to a 100 mL hydrothermal reactor and reacted at 180°C for 6 h. After the reaction, centrifugation was performed, and the supernatant was filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate was transferred to a dialysis bag with a molecular cutoff of 500 Da and dialyzed for 48 h to obtain a carbon quantum dot solution, named 4C-CQDs.

[0040] Figure 2 These are TEM images of the 4C-LNPs prepared in Example 1, from... Figure 2 It can be seen that the lignin nanoparticles prepared by the direct solvent nanoprecipitation method of the present invention are well dispersed and have a spherical structure.

[0041] Table 1 shows the yield and weight-average molecular weight of sugarcane bagasse lignin. As can be seen from Table 1, the yield of 4C-L is 13.44 ± 0.54%, and the Mw is 2365 g / mol.

[0042] Table 2 shows the Zeta potential and hydration kinetic size of lignin nanoparticles. As can be seen from Table 2, the Zeta potential of 4C-LNPs is -27.75±0.43mV and the hydration kinetic size is 971.92±60.70nm, indicating that 4C-LNPs have good stability and small particle size.

[0043] Figure 3 These are TEM images of the 4C-CQDs prepared in Example 1, by... Figure 3It can be seen that the present invention successfully synthesized carbon quantum dots by hydrothermal method. The carbon quantum dots have an approximately spherical appearance and good dispersibility in aqueous solution. The average diameter is 10.91±3.69nm. High-resolution TEM further revealed its microstructure. The 4C-CQDs have clear lattice stripes and a lattice spacing of 0.21nm, which corresponds to the (100) crystal plane of graphene, indicating that the prepared carbon quantum dots have structural features similar to graphene.

[0044] Figure 4 These are photographs of the 4C-CQDs solution prepared in Example 1 under different illuminations and fluorescence spectra at different excitation wavelengths. Figure 4 It can be seen that the 4C-CQDs solution emits bright blue fluorescence under ultraviolet light irradiation, which is a typical carbon quantum dot photoluminescence phenomenon. As the excitation wavelength increases, the fluorescence emission wavelength shows a red shift, which is wavelength-dependent. Moreover, the fluorescence intensity of 4C-CQDs at an excitation wavelength of 316 nm is stronger than that of other examples and comparative examples.

[0045] Figure 5 This is the XPS image of the 4C-CQDs prepared in Example 1, by... Figure 5 It can be seen that nitrogen element has been successfully doped into carbon quantum dots.

[0046] Figure 6 The 4C-CQDs prepared in Example 1 are subjected to different concentrations of Fe. 3+ The fluorescence spectrum and linear relationship diagram are derived from... Figure 6 It can be seen that the fluorescence intensity change (F0-F1) is related to Fe 3+ The linear relationship between concentrations is: y = 0.1031x + 17.133 (where x is Fe). 3+ The concentrations, F0 and F1, represent the addition of Fe, respectively. 3+ The fluorescence intensity of 4C-CQDs before and after the reaction was measured. The correlation coefficient of the linear regression was 0.9933, indicating a high linear fit and good fitting effect. The 4C-CQDs prepared in this invention can be used in Fe... 3+ It exhibits excellent sensitivity in inspection, enhancing its application potential in fields such as food safety, environmental monitoring, and bioimaging.

[0047] Example 2:

[0048] A method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, specifically including the following steps:

[0049] (1) Mix choline chloride, oxalic acid dihydrate and ethylene glycol in a molar ratio of 1:2:1 and stir in a 90°C water bath for 2 hours until all components are completely dissolved and uniformly mixed. Name it 2C-DES.

[0050] (2) Sugarcane bagasse and 2C-DES were added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20. The mixture was heated at 100°C for 5 hours. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70 wt% ethanol solution. The mixture was stirred at room temperature for 2 hours and then vacuum filtered. The filtrate was evaporated at 40°C and 90 mbar to obtain a lignin-eutectic solvent mixture.

[0051] (3) Add 10 times the volume of deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir for 1 hour. After standing and settling for 10 hours, filter again and wash the obtained solid to obtain sugarcane bagasse lignin (2C-L) and eutectic solvent aqueous solution.

[0052] (4) Dissolve 2C-L in anhydrous ethanol to prepare a concentration of 1 mg / mL. Filter through a 0.45 μm PTFE filter to remove insoluble matter. Then, add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to make the ethanol concentration 50% to obtain lignin nanoparticles, named 2C-LNPs.

[0053] (5) The eutectic solvent aqueous solution obtained in step (3) was rotary evaporated at 40°C and 90 mbar to remove excess water. Then, it was transferred to a 100 mL hydrothermal reactor and reacted at 200°C for 8 h. After the reaction, centrifugation was performed, and the supernatant was filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate was transferred to a dialysis bag with a molecular cutoff of 1000 Da and dialyzed for 60 h to obtain a carbon quantum dot solution, named 2C-CQDs.

[0054] The yield of 2C-L obtained in this embodiment was 8.37±0.09%, the Mw was 2369 g / mol, the Zeta potential of 2C-LNPs was -16.78±0.47 mV, and the hydration kinetic size was 1229.80±25.27 nm.

[0055] Example 3:

[0056] A method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, specifically including the following steps:

[0057] (1) Mix choline chloride, oxalate dihydrate and 1,3-propanediol in a molar ratio of 1:1:1 and stir in a water bath at 100°C for 3 hours until all components are completely dissolved and uniformly mixed. Name it 3C-DES.

[0058] (2) Sugarcane bagasse and 3C-DES were added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20. The mixture was heated at 120°C for 6 hours. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70 wt% ethanol solution. The mixture was stirred at room temperature for 2 hours and then vacuum filtered. The filtrate was evaporated by rotary evaporation at 40°C and 90 mbar to obtain a lignin-eutectic solvent mixture.

[0059] (3) Add 10 times the volume of deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir for 2 hours. After standing and settling for 12 hours, filter again and wash the obtained solid to obtain sugarcane bagasse lignin (3C-L) and eutectic solvent aqueous solution.

[0060] (4) Dissolve 4C-L in anhydrous ethanol to prepare a concentration of 1 mg / mL. Filter through a 0.45 μm PTFE filter to remove insoluble matter. Then, add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to make the ethanol concentration 50% to obtain lignin nanoparticles, named 3C-LNPs.

[0061] (5) The eutectic solvent aqueous solution obtained in step (3) was rotary evaporated at 40°C and 90 mbar to remove excess water. Then, it was transferred to a 100 mL hydrothermal reactor and reacted at 220°C for 10 h. After the reaction, centrifugation was performed, and the supernatant was filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate was transferred to a dialysis bag with a molecular cutoff of 3000 Da and dialyzed for 72 h to obtain a carbon quantum dot solution, named 3C-CQDs.

[0062] The yield of 3C-L obtained in this embodiment was 14.36±0.21%, Mw was 2013 g / mol, the Zeta potential of 3C-LNPs was -22.65±1.38 mV, and the hydration kinetic size was 1156.24±30.67 nm.

[0063] Example 4:

[0064] A method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, specifically including the following steps:

[0065] (1) Mix choline chloride, oxalate dihydrate and 1,5-pentanediol in a molar ratio of 1:2:1 and stir in a 90°C water bath for 1 hour until all components are completely dissolved and uniformly mixed. Name it 5C-DES.

[0066] (2) Sugarcane bagasse and 5C-DES were added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20. The mixture was heated at 120°C for 4 hours. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70 wt% ethanol solution. The mixture was stirred at room temperature for 2 hours and then vacuum filtered. The filtrate was evaporated at 40°C and 90 mbar to obtain a lignin-eutectic solvent mixture.

[0067] (3) Add 10 times the volume of deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir for 0.5 h. After standing and settling for 12 h, filter again and wash the obtained solid to obtain bagasse lignin (5C-L) and eutectic solvent aqueous solution.

[0068] (4) Dissolve 5C-L in anhydrous ethanol to prepare a concentration of 1 mg / mL. Filter through a 0.45 μm PTFE filter to remove insoluble matter. Then, add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to make the ethanol concentration 50% to obtain lignin nanoparticles, named 5C-LNPs.

[0069] (5) The eutectic solvent aqueous solution obtained in step (3) was rotary evaporated at 40°C and 90 mbar to remove excess water. Then, it was transferred to a 100 mL hydrothermal reactor and reacted at 220°C for 6 h. After the reaction, centrifugation was performed, and the supernatant was filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate was transferred to a dialysis bag with a molecular cutoff of 500 Da and dialyzed for 72 h to obtain a carbon quantum dot solution, named 5C-CQDs.

[0070] The yield of 5C-L obtained in this embodiment was 13.42±0.49%, the Mw was 2827 g / mol, the Zeta potential of 5C-LNPs was -28.37±0.45 mV, and the hydration kinetic size was 1050.67±40.10 nm.

[0071] Comparative example:

[0072] A method for preparing sugarcane bagasse lignin nanoparticles and carbon quantum dots, specifically including the following steps:

[0073] (1) Mix choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, stir in a 90°C water bath for 1 hour until all components are completely dissolved and uniformly mixed, and name it OC-DES.

[0074] (2) Sugarcane bagasse and OC-DES were added to a thick-walled stoppered test tube at a solid-liquid ratio of 1:20. The mixture was heated at 120°C for 4 hours. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70 wt% ethanol solution. The mixture was stirred at room temperature for 2 hours and then vacuum filtered. The filtrate was evaporated by rotary evaporation at 40°C and 90 mbar to obtain a lignin-eutectic solvent mixture.

[0075] (3) Add 10 times the volume of deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir for 0.5 h. After standing and settling for 12 h, filter again and wash the obtained solid to obtain sugarcane bagasse lignin (OC-L) and eutectic solvent aqueous solution.

[0076] (4) Dissolve OC-L in anhydrous ethanol to prepare a concentration of 1 mg / mL. Filter through a 0.45 μm PTFE filter to remove insoluble matter. Then, add deionized water dropwise to the sugarcane bagasse lignin ethanol solution to make the ethanol concentration 50% to obtain lignin nanoparticles, named OC-LNPs.

[0077] (5) The eutectic solvent aqueous solution obtained in step (3) was rotary evaporated at 40°C and 90 mbar to remove excess water. Then, it was transferred to a 100 mL hydrothermal reactor and reacted at 220°C for 6 h. After the reaction, centrifugation was performed, and the supernatant was filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate was transferred to a dialysis bag with a molecular cutoff of 500 Da and dialyzed for 72 h to obtain a carbon quantum dot solution, named OC-CQDs.

[0078] The yield of 0C-L obtained in this comparative example was 12.70±0.75%, with a Mw of 1468 g / mol. The zeta potential of 0C-LNPs was -7.13±0.40 mV, and the hydration kinetic size was 30947.10±33.21 nm. The fluorescence intensity was lowest at an excitation wavelength of 316 nm, indicating that the addition of diol can improve the stability of the obtained LNPs, reduce the particle size, and is more beneficial for subsequent applications of lignin nanoparticles and carbon quantum dots.

[0079] Table 1. Yield and weight-average molecular weight of lignin from sugarcane bagasse

[0080]

[0081] As shown in Table 1, the yield of lignin from sugarcane bagasse ranged from 8.37% to 13.44%. The lowest yield was obtained with 2C-L in Example 2, at 8.37 ± 0.99%. This is because the side chains of lignin were modified after pretreatment with a diol eutectic solvent, improving their solubility and making some lignin unrecoverable by simple precipitation, thus causing the difference in the yield of sugarcane bagasse lignin. Compared to the comparative example OC-L, the molecular weight of the sugarcane bagasse lignin in Examples 1-4 was higher than that of OC-L, indicating that the diol helped protect the β-O-4 bonds in the lignin molecule and inhibited lignin condensation. This was influenced by factors such as the pretreatment conditions of the eutectic solvent and the source of biomass. The sugarcane bagasse lignin obtained in the examples of this invention has a more uniform molecular weight (Mw) (2013-2827 g / mol), reducing the heterogeneity of lignin and helping to maintain its integrity.

[0082] Table 2. Zeta potential and hydration kinetics of lignin nanoparticles

[0083]

[0084] The embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A carbon quantum in heavy metal Fe 3+ Its application in security detection is characterized by, The application method is as follows: based on the fluorescence intensity of the carbon quantum dot solution with respect to Fe... 3+ The concentration of Fe decreases with increasing concentration and shows a linear correlation, thus obtaining the Fe concentration in the system. 3+ The concentration of carbon quanta is prepared according to the following steps: (1) Preparation of diol eutectic solvent: Choline chloride, oxalic acid dihydrate and diol are mixed in a molar ratio of 1:1-2:0.2-1, heated in a water bath at 80-100 ℃, and stirred for 1-3 h until all components are completely dissolved and uniformly mixed to obtain diol eutectic solvent; the diol is one of ethylene glycol, 1-3 propylene glycol, 1-4 butanediol and 1-5 pentanediol; (2) Sugarcane bagasse pretreatment: Sugarcane bagasse and diol eutectic solvent were added to a thick-walled stoppered test tube with a solid-liquid ratio of 1:20 and heated at 80-120 °C for 4-6 h. After the reaction was completed, the treatment solution was transferred to a beaker with 100 mL of 70wt% ethanol solution and stirred at room temperature for 2 h before vacuum filtration. After pretreatment, an aqueous ethanol solution was added to the system and stirred. Then, the ethanol in the filtrate was removed by filtration and rotary evaporation to obtain a lignin-eutectic solvent mixture. The rotary evaporation conditions were 40 °C and 90 mbar. (3) Separation of lignin: Add deionized water to the lignin-eutectic solvent mixture obtained in step (2) and stir. After settling, filter again and wash the solid to obtain bagasse lignin and eutectic solvent aqueous solution. (4) Preparation of carbon quantum dots: The eutectic solvent aqueous solution obtained in step (3) is subjected to rotary evaporation to remove excess water, and then transferred to a hydrothermal reactor for hydrothermal reaction. After dialysis and filtration, carbon quantum dot solution CQDs is obtained. The hydrothermal reaction temperature is 180-220 ℃ and the time is 6-10 h.

2. The carbon quantum in heavy metal Fe as described in claim 1 3+ Applications in security detection, characterized by In step (3), the volume of deionized water added is 10 times the volume of lignin-eutectic solvent, and the mixture is stirred for 0.5-2 h and allowed to settle for 8-12 h.

3. The carbon quantum in heavy metal Fe as described in claim 1 3+ Applications in security detection, characterized by In step (4), the rotary evaporation conditions are 40 °C and 90 mbar. After the reaction is completed, centrifugation is performed, and the supernatant is filtered through a 0.22 μm filter membrane to remove insoluble carbon, resulting in a light yellow filtrate. Subsequently, the filtrate is transferred to a dialysis bag with a molecular cutoff of 500-3000 Da, and deionized water is used as the dialysis solution. The dialysis time is 48-72 h.

Citation Information

Patent Citations

  • Method for extracting lignin by using ternary eutectic solvent

    CN115232176A

  • Preparation method of green fluorescence emission carbon quantum dots with high quantum yield

    CN115678551A

  • Method for extracting cotton stalk lignin by ultrasonic-assisted choline chloride-formic acid eutectic solvent

    CN116716751A

  • Method for separating biomass components by using ternary eutectic solvent

    CN117683244A